Vitamin D composition of Australian game products - Dunlop, Eleanor; Shepherd, Carrington; Cunningham, Judy; Strobel, N.; Lucas, R.M.; Black, Lucinda (ELSEVIER SCI LTD, 2022)
The vitamin D content of many Australian game products is unknown. These foods are potential sources of vitamin D for remote-dwelling Aboriginal and Torres Strait Islander people, of whom 39% are vitamin D deficient (serum 25-hydroxyvitamin D3 (25(OH)D3) concentrations < 50 nmol/L). Vitamin D3, 25(OH)D3, vitamin D2 and 25(OH)D2 were measured by liquid chromatography-triple quadrupole mass spectrometry (LC-QQQ) in raw meat (camel, crocodile, emu, kangaroo), emu eggs and emu oil. Vitamin D3 (range, 0.5–14.5 μg/100 g) was found in all products except camel and kangaroo. All samples except kangaroo contained 25(OH)D3; some camel samples contained relatively high concentrations (range, 0.4–5.2 μg/100 g). Vitamin D2 was found in emu products and some kangaroo samples. We detected trace amounts of 25(OH)D2 in some camel and kangaroo samples. This study provides valuable insight into foods with a paucity of data on vitamin D content, showing that some are potentially useful sources of vitamin D.